PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA CANVA TERHADAP HASIL BELAJAR MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS V SEKOLAH DASAR - Rezza Risky Fadila; Rika Perdana , Dayu; Dwi Oktaria , Sheren; Sowiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Canva media on the learning outcomes of fifth-grade students in the Pancasila Education subject at SD Negeri 1 Gunung Agung. The problem in this study is the low learning outcomes of students caused by conventional learning practices and the limited use of engaging learning media. The research employed a quasi-experimental design with a nonequivalent control group design. The population consisted of 65 students, including 33 students in the control class and 32 students in the experimental class. Data collection techniques included observation, documentation, and learning outcome tests in the form of pretest and posttest. Data analysis used normality test, homogeneity test, N-gain test, and simple linear regression test. The results showed that the Problem Based Learning (PBL) model assisted by Canva media had a significant effect on students’ learning outcomes, with a significance value of 0.000 < 0.05 and an R Square value of 0.447. In addition, the N-gain results indicated that the experimental class obtained a score of 0.34 in the moderate category, while the control class obtained 0.18 in the low category. Thus, the Problem Based Learning (PBL) model assisted by Canva media positively affects the Pancasila Education learning outcomes of fifth-grade students at SD Negeri 1 Gunung Agung.